Impeded industrial restructuring: The growth penalty - David B. Audretsch; Martin A. Carree; André J. van Stel; A. Roy Thurik (Hamburg Institute of International Economics (HWWA), 2000)
This paper documents that a process of industrial restructuring has been transforming the developed economies, where large corporations are accounting for less economic activity and small firms are accounting for a greater share of economic activity. Not all countries, however, are experiencing the same shift in their industrial structures. Very little is known about the cost of resisting this restructuring process. The goal of this paper is to identify whether there is a cost, measured in terms of forgone growth, of an impeded restructuring process. The cost is measured by linking growth rates of OECD countries to deviations from the optimal industrial structure. The empirical evidence suggests that countries impeding the restructuring process pay a penalty in terms of forgone growth. – – Dieses Diskussionspapier dokumentiert einen Strukturwandel, der zur Transformation der Wirtschaften hochentwickelter Länder führt: Großunternehmen verlieren gegenüber den kleineren Firmen relativ an Gewicht. Dieser Strukturwandel erfolgt in den einzelnen Ländern in unterschiedlichem Maße. Sehr wenig ist über die Konsequenzen bekannt, die entstehen, wenn ein Land sich dem Strukturwandel verweigert. Ziel dieses Papiers ist eine Einschätzung möglicher Kosten, die durch Behinderung des Strukturwandels entstehen. Derartige Kosten werden gemessen, indem die Wachstumsrate der OECDLänder den Abweichungen von einer "optimalen" Unternehmensstruktur gegenübergestellt werden. Die empirische Evidenz legt die Vermutung nahe, dass Länder, welche den Strukturwandel behindern, eine "Strafe" in Form von Wachstumseinbußen bezahlen.
Keywords: L11; O11; 330; Industry structure; firm size distribution; entrepreneurship; economic growth; Industrieller Strukturwandel; Strukturpolitik; Wirtschaftliche Anpassung; Wirtschaftswachstum; Betriebsgröße; Unternehmer; OECD-Staaten